Understanding Distortion of Islam Nusantara on Public Opinion in Indonesia on Political Ambience of 2019 Presidential Election - Kiki Esa Perdana (INC- Islam Nusantara Center, 2019)
One of the most important roles in communication in life is that the information that is received is not distorted; moreover it can be received by the communicator completely. With a good plot of communication, all the process of information flows and good will from Islam Nusantara will be considered smooth and succeed. Communication effect or feedback is very important for all the information flows without exception so that the final result that is gained is really appropriate. In the end, all those people who have role to convey the communication activity of Islam Nusantara must pass through the process diligently; because it is definitely that the communication process of Islam Nusantara will be distorted, with so many unsubstantial disagreements emerge.